Surrogate species in pesticide risk assessments: Toxicological data of three stingless bees species - Lourencetti, Ana Paula Salomé; Azevedo, Patricia; Miotelo, Lucas [UNESP]; Malaspina, Osmar [UNESP]; Nocelli, Roberta Cornélio Ferreira (Elsevier, 2023)
Discussions about environmental risk reassessment of pesticides have grown in the last decades, especially in tropical and subtropical regions since the diversity of bee species in these places is quite different. Stingless bees are highly affected by pesticides, and toxicity information is necessary to include them in the regulatory process of countries that hosts a diversity of these species. Therefore, the present study aimed to evaluate the Median Lethal Concentration (LC50), estimate the Median Lethal Dose (LD50) and compared the sensitivity of three species of stingless bees exposed to the commercial formulation of the neonicotinoid thiamethoxam (TMX). The LD50 was estimated based on the LC50 determined in the present study (LC50 = 0.329 ng a.i./μL for Tetragonisca angustula; 0.624 ng a.i./μL for Scaptotrigona postica, and 0.215 ng a.i./μL for Melipona scutellaris). Considering these data, toxicity endpoints were used to fit species sensitive distribution curves (SSD) and determine the sensitivity ratio. The results showed that all the stingless bees tested are more sensitive to TMX than the Apis mellifera, the model organism used in ecotoxicological tests. Regarding the oral LC50, the most susceptible and most tolerant species were M. scutellaris > T. angustula > S. postica > A. mellifera. Following the same evaluated pattern, for the LD50 (considering the weight of the bees - ng a.i./g bee), we have: M. scutellaris > S. postica > T. angustula > A. mellifera, and without the weight considered (ng a.i./bee): T. angustula > M. scutellaris > S. postica > A. mellifera. The different sensitivities among stingless bee species highlight the importance of inserting more than one surrogate species with a variety of sizes in research and protocol development. Additionally, the research suggests the need to investigate patterns regarding the influence of body mass on pesticide sensitivity among stingless bee species.
Keywords: Body weight; LC50; LD50; Neonicotinoids; Species Sensitivity Distribution (SSD); Thiamethoxam